Digital Finance and Firm Exit: Mathematical Model and Empirical Evidence from Industrial Firms - Fenfen Ma; Linxing Lei; Ziyang Chen; Mancang Wang (Discrete Dynamics in Nature and Society)
From the perspective of financial constraint, this paper constructs a mathematical model to analyze the impact of digital financial development on firm exit probability. The relationship between digital finance and firm exit was tested empirically based on the industrial firm data in 2011–2013. The results show that digital financial development significantly suppresses firm exit probability. Mechanism analysis suggests that digital financial development can ease the information asymmetry of the credit market, facilitate the credit acquisition of firms, and alleviate the constraint on corporate financing, thereby reducing the probability of firm exit. This paper provides the theoretical basis and empirical evidence for controlling firm exit from the angle of digital finance development.